2014
DOI: 10.1177/0960327113497773
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of low-shrink composites with new monomer technology on bovine dental pulp-derived cells

Abstract: Objectives: The aim of this study was to evaluate the cytotoxicity of four low-shrink composites with new monomer technology on the bovine dental pulp-derived cells (bDPCs). Materials and methods: Ten samples were prepared for each group composites, and the samples were immersed in 7 mL of culture medium for 72 h at 37°C to extract residual monomer or cytotoxic substances. The culture medium containing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2016
2016
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
0
5
0
1
Order By: Relevance
“…It has been demonstrated that resin cements present toxic reaction in cell cultures by unreacted monomers released from the material during the polymerization reaction, which is related to thickness, light intensity, and photoactivation times of the material 8,12 . Is has also been demonstrated that comonomers, additives, and reaction products are released from polymerized cements 12,18 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been demonstrated that resin cements present toxic reaction in cell cultures by unreacted monomers released from the material during the polymerization reaction, which is related to thickness, light intensity, and photoactivation times of the material 8,12 . Is has also been demonstrated that comonomers, additives, and reaction products are released from polymerized cements 12,18 .…”
Section: Discussionmentioning
confidence: 99%
“…Is has also been demonstrated that comonomers, additives, and reaction products are released from polymerized cements 12,18 . According to Ferracane 15 , 2013, cytotoxic effects are associated with incomplete polymerization reaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Resin composite materials were applied carefully into a circumferential teflon mold with the same specimen dimensions positioned onto a 0.05 mm-thick transparent polyester filmstrip (Mylar, DuPont, and Wilmington, DE, USA) over a glass slide. Materials were covered with another celluloid strip, and the glass slide weighed of 200 g for 1 minute until the slide touched the mold completely, thus allowing excess composite to flow prior to curing (21) and to minimize the oxygen inhibition and maximize the surface smoothness (16). The distance between the light and the specimen was also standardized by using this 1-mm glass slide (22).…”
Section: Methodsmentioning
confidence: 99%
“…Several low shrinking resin composites have been introduced (13,15). According to the manufacturers’ information, the filler content and polymerization shrinkage rate of these low-shrinkage composite resin restorative materials are different from those of the conventionally used composites (12,16). …”
Section: Introductionmentioning
confidence: 99%